2020
DOI: 10.1039/c9gc02669j
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of chitin to levulinic acid catalyzed by ionic liquids: distinctive effect of N-acetyl groups

Abstract: Selective and green conversion of chitin to levulinic acid has been realized by catalysis of ionic liquids up to a yield of 67.0%. Two-approach mechanism was proposed in the presence of H-bonding networks mainly contributed by the N-acetyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Interestingly, the use of ILs with acidic sulfonic group that are usually used as dehydration agents in similar reactions as catalysts required increase in the reaction temperature and resulted in bond cleavage with formation of formic and levulinic acids, and not deoxyfructosazine (Wang et al, 2016). Recently, selective transformation of chitin and chitosan into levulinic acid has been realized by the catalysis using acidic 1-methyl-3-(3-sulfopropyl)imidazolium hydrogen sulfate ([HSO 3 C 3 mim][HSO 4 ]) up to a yield of 67.0% (Hou et al, 2019). The authors suggested the IL was not basic enough to completely disrupt H-bonding of the N-acetyl groups which shielded the accessibility of glycosidic linkages to the acidic catalyst, thus deacetylation-depolymerization mechanisms occurred only at the outer surface of the polymer.…”
Section: Preparation Of Complex Compoundsmentioning
confidence: 99%
“…Interestingly, the use of ILs with acidic sulfonic group that are usually used as dehydration agents in similar reactions as catalysts required increase in the reaction temperature and resulted in bond cleavage with formation of formic and levulinic acids, and not deoxyfructosazine (Wang et al, 2016). Recently, selective transformation of chitin and chitosan into levulinic acid has been realized by the catalysis using acidic 1-methyl-3-(3-sulfopropyl)imidazolium hydrogen sulfate ([HSO 3 C 3 mim][HSO 4 ]) up to a yield of 67.0% (Hou et al, 2019). The authors suggested the IL was not basic enough to completely disrupt H-bonding of the N-acetyl groups which shielded the accessibility of glycosidic linkages to the acidic catalyst, thus deacetylation-depolymerization mechanisms occurred only at the outer surface of the polymer.…”
Section: Preparation Of Complex Compoundsmentioning
confidence: 99%
“…[66][67][68][69][70] Chitin is the most abundant amino polysaccharide and is obtained from the shells of shrimp, sh, and crabs. 71,72 Chitosan has desirable properties such as non-toxicity, biocompatibility, biodegradability, hemostatic activity, cell adhesion, anti-inammatory properties, antimicrobial effect, and activity against various types of bacteria and fungi, which makes it a suitable polymer and it has been effective in tissue engineering, drug delivery systems and wound healing. [73][74][75] Aer wounding, cells die and extensive tissue damage occurs, and neutrophils, which contain high amounts of degrading enzymes and oxygen free radicals, release these substances into the wound environment, prolonging the inammatory phase.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin and its monomer NAG have been converted into some value‐added compounds, such as 5‐hydroxymethylfurfural (5‐HMF), 5‐(chloromethyl)furfural (CMF), levulinic acid (LA), formic acid and acetic acid, etc. [9–16] . Unfortunately, these compounds do not retain the unique nitrogen element of chitin or NAG, wasting valuable N resources.…”
Section: Introductionmentioning
confidence: 99%